Differences in School Performance Between Only Children and Non-only Children: Evidence From China - Jia, Chaochao; Yang, Zhaoxi; Xin, Tao; Li, Youfa; Wang, Yehui; Yang, Tao (Frontiers in Psychology, 2022)
The present study aimed to investigate the features of only-child status in different perspectives, related to physical health, math achievement and school feelings and expectations. A representative sample of 91,619 grade 4 students with an average age of 10.4 ± 0.7, among which 28,631 only children，were assessed. We used propensity score matching and the average treatment effects on the treated to analyze data. The treatment was the only-child of a family. The results indicated that only children had better academic achievement, cardiorespiratory fitness and feelings toward school whereas non-only children had better physical status and anaerobic fitness. In addition, sex and rural versus urban areas differences were also explored, and the adverse situation for rural only-boys is warmed for families, researchers and governments. Some suggestions are given under the Two-child Policy.